Tribalism: Thorny issue towards reconciliation in South Africa – A practical theological appraisal - Baloyi, Elijah ca. 20./21. Jh. (HTS teologiese studies, 2018)
The apartheid regime used various strategies to ensure that South Africans formed a divided nation. It was through the differences between ethnic groups and tribes, among other things, that the government of the time managed to manipulate and entrench hatred and a lack of trust among most black South Africans. Tribalism, which existed even before apartheid, became instrumental in inflicting those divisions as perpetuated by the formation of homelands. The various ethnic groups had been turned against one other, and it had become a norm. Nepotism, which is part and parcel of the South African government, is just an extension of tribalism. It is the objective of this article to uncover how tribalism is still rearing its ugly head. From a practical theological perspective, it is important to deal with tribalism as a tool that plays a part in delaying tribal reconciliation, which was orchestrated by apartheid policies in South Africa.